Influência do tamanho e forma na qualidade das sementes de milho durante armazenamento - Jurach, Jorge José (2004)
Corn, a species originating from the Americas, adapted by researchers to different climatic conditions and planting seasons, has great importance in the world economic context. The mass production of seeds aims to the maximum utilization of raw materials and to facilitate and make uniform planting. Seeds are classified according to their diverse size to the shapes and attempt to offer the market a homogenous. Product, and one which is easy for seeders to distribute. The quality of seeds, mainly that of the smaller and round ones, has been questioned by farmers on account of the frequency of emergency and field establishment problems. With the objective of evaluating the quality of the super precocious hybrid corn CD 304, a study was conducted at COODETEC in Cascavel-PR. For it, seeds from commercial lots of the flat grade seeds 18C, 20C and 22C, as well as ones from the round-shaped grades 18R, 20R and 22R coming from the harvest of 2001/2002, were used. For four seasons, beginning in August 2002, every three months, first count, germination pattern, viability cold, and soil emergency tests were conducted to evaluate the germination capacity and vigour and sanity, humidity, and the mass of a thousand seeds tests were also carried out in order to attend to the sanitary and physical conditions of the seeds during the storage period. The soil emergency test was effected in greenhouses covered with transparent plastic. The experimental delineation was entirely casual for all of the tests. From the analysis of the obtained results, maitenance of quality was verified for a greater period in the median grades (the flat 20C and 22C, and 20R) there by indicating their greater longetivity and vigour. The round grades 18R and 22R and the flat one of lesser mass, 18C, showed less vigour and longetivity